Failure to detect the anti-mutagenic effect of insulin in experimental type-2 diabetic rats (Journal of Pharmaceutical Negative Results, 2010)
Background: The oxidative stress is known to cause mutation-related disordersin diabetic patients. Materials and Methods: The present study was designed toinvestigate the anti-mutagenic effect of insulin in nicotinamide (NA: 230 mg/kg,i.p.) and streptozotocin (STZ: 65 mg/kg, i.p.) induced nuclear defects. Bone marrowmicronucleus (MN) test and caudal epididymal sperm abnormalities were detected tofind the somatic and germinal cell mutations, respectively. The antioxidant status wasdetermined by estimating serum lipid peroxidation, catalase, superoxide dismutase andglutathione peroxidase levels. Results: The experimental type diabetes significantly(P < 0.001) reduced the antioxidant status and enhanced MN frequency and spermdefects compared to control animals. Although administration of insulin (1, 3, 5 and7 IU/kg, s.c. for 4 weeks) significantly (P < 0.001) reduced hyperglycemia, it didnot alter the antioxidant status, and somatic and germinal cell defects in diabetic rats.Conclusion: The results suggest that insulin did not have protective effect againstthe genotoxicity induced by NA-STZ diabetes.